High-damping repairable hydrogel as well as preparation method and application thereof

By selecting suitable monomers and additives in the hydrogel to form hydrogen bond networks and salt responsiveness, the problem of insufficient energy dissipation under high-strength impact is solved, and a high-strength and self-healing hydrogel material is achieved, which improves its mechanical properties and service life.

CN119823413APending Publication Date: 2025-04-15NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411707569.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When faced with high-intensity impact, existing damping hydrogels cannot effectively dissipate energy, and it is difficult to take into account high-strength mechanical properties and self-restoration capabilities.

Method used

By selecting methacrylamide and hydroxyethyl acrylate as monomers, a dense hydrogen bond network is formed, and a high-damping repairable hydrogel is prepared by combining the salt responsiveness and self-healing properties of boric acid. The hydrogel regulates its rheological properties and self-healing ability through a salt solution to form a glassy state to improve mechanical properties.

Benefits of technology

It realizes high-strength hydrogel material, has self-healing properties, can effectively avoid loss of hydrogel during energy dissipation, and improves its service life and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823413A_ABST
    Figure CN119823413A_ABST
Patent Text Reader

Abstract

The invention provides repairable high-damping hydrogel and a preparation method thereof, and relates to the field of materials.The repairable high-damping hydrogel is prepared from methacrylamide, a hydroxyethyl acrylate monomer, boric acid, a salt solution and an initiator, and the mass ratio of methacrylamide to the hydroxyethyl acrylate monomer is 8: 1; the sum of the mass percentage contents of methacrylamide and hydroxyethyl acrylate monomers is taken as a main body, the mass of the initiator is 0.5% of the mass of the main body, the mass of the boric acid is 1.8% of the mass of the main body, and the concentration of the salt solution is 1mol / L. The preparation method of the damping material comprises the following steps: heating a precursor solution to react to obtain gel; the gel is soaked in a salt solution to obtain the damping gel, and the damping gel can have repairability through salt treatment. The gel provided by the invention has the advantages of high damping and repairability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel materials, and in particular relates to a high-damping repairable hydrogel and a preparation method and application thereof. Background Art

[0002] Damping materials, due to their efficiency in absorbing energy and reducing vibration, play a significant role in reducing noise, vibration and shock. Such materials play a key role in industries such as aerospace, automobile manufacturing, military and electronics. In production and life, different types of vibration and noise are generated due to various reasons. They will bring many negative effects, including reducing signal quality, causing structural damage and shortening equipment life. Therefore, high-performance damping materials are widely used to eliminate these vibrations. Damping materials convert these vibrations into internal energy through repeated deformation, which can effectively dissipate energy and reduce amplitude, thereby protecting material devices.

[0003] In recent years, hydrogel materials, as a unique soft material, have good biocompatibility and can dissipate energy well due to their high water content and excellent viscoelasticity. They have great potential as damping materials. However, their mechanical properties need to be improved, and once most traditional hydrogels are damaged, their internal structures are difficult to self-recover, which not only affects the service life of the hydrogel, but also limits its reliability and stability under long-term use conditions. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the existing damping hydrogel cannot effectively dissipate energy when facing high-intensity impact and cannot take into account high-strength mechanical properties, and to provide a high-strength and tough hydrogel material with self-repairing properties, which can well avoid the loss of hydrogel when used as an energy dissipation carrier.

[0005] The invention provides a high-damping repairable hydrogel, which comprises the following raw materials: methacrylamide, hydroxyethyl acrylate monomer, boric acid, a salt solution and an initiator, wherein the mass ratio of the methacrylamide to the hydroxyethyl acrylate monomer is 8:1, the sum of the mass percentages of the methacrylamide and the hydroxyethyl acrylate monomer is taken as the main body, the mass of the initiator is 0.5% of the mass of the main body, the mass of the boric acid is 1.8% of the mass of the main body, and the concentration of the salt solution is 1 mol / L.

[0006] Compared with the prior art, in the design of the damping hydrogel of the present invention, by selecting monomers of methacrylamide and hydroxyethyl acrylate, a dense hydrogen bond network is formed, which provides good mechanical strength. At the same time, methacrylamide has obvious salt responsiveness, and its rheological properties can be regulated by different salts. In addition, the introduction of borate bonds makes the hydrogel have self-repairing properties, and its performance is improved by salting out salt to make it enter a glassy state. When necessary, the sodium bisulfate salt solution is used to restore the dynamics of the chain to provide self-repairing properties.

[0007] In some embodiments, the salt solution is selected from at least one of a potassium sulfate solution, a sodium sulfate solution, a sodium citrate solution, and a sodium bisulfate solution.

[0008] The present invention provides a moderate ionic strength by setting the concentration of the salt solution to 1 mol / L, which is crucial for controlling the rheological properties and self-healing ability of the hydrogel. Too high a salt concentration may cause the hydrogel to be over-crosslinked and become too rigid; while too low a salt concentration may not effectively promote the hydrogel to enter the glassy state, affecting its mechanical properties and self-healing ability.

[0009] In some embodiments, the initiator is ammonium persulfate and / or potassium persulfate.

[0010] Compared with the prior art, the present invention selects the above-mentioned initiator for the following purpose: ammonium persulfate and potassium persulfate are both strong oxidants, which can decompose in aqueous solution to generate free radicals. These free radicals can initiate the polymerization reaction of methacrylamide (MA) and 2-hydroxyethyl acrylate (HEA) to form a polymer network; at the same time, persulfate initiators can rapidly decompose at room temperature or under heating conditions to generate free radicals, ensuring that the polymerization reaction starts quickly, thereby improving the synthesis efficiency.

[0011] The second object of the present invention is to provide a method for preparing a high-damping repairable hydrogel, the preparation method specifically comprising the following steps:

[0012] Using water as solvent, methacrylamide, hydroxyethyl acrylate, boric acid and initiator are dissolved in water to prepare a polymerization precursor solution, the polymerization precursor solution is poured into a parallel glass plate mold for heating treatment to obtain a gel, and then the gel is post-treated with a salt solution to obtain a high-damping repairable hydrogel.

[0013] Compared with the prior art, the entire preparation process of the present invention, from the preparation of the polymerization precursor solution to the formation of the final hydrogel, has simple and clear operation steps and is easy to control.

[0014] In some embodiments, the mass of the water is 60-70% of the mass of the body.

[0015] Compared with the prior art, the present invention uses the above-mentioned water content to ensure that the monomers and other components are fully dissolved and evenly dispersed in water, avoiding local aggregation and uneven polymerization caused by excessive concentration; at the same time, within this water content range, the viscosity of the precursor liquid is moderate, neither too thin to cause excessive fluidity nor too viscous to cause mixing difficulties. This helps to form a uniform gel layer in the mold.

[0016] In some embodiments, the pH of the polymerization precursor solution is 9.

[0017] Compared with the prior art, the present invention adopts the polymerization precursor solution of the above pH system because: under the condition of pH 9, the solubility of methacrylamide (MA) and hydroxyethyl acrylate (HEA) will be improved, which is conducive to forming a uniform precursor solution. This can avoid the local aggregation of monomers in water and ensure the uniform progress of the polymerization reaction; at the same time, in an alkaline environment, the stability of the monomers is better, and it is not easy to spontaneously polymerize or degrade, thereby extending the service life of the precursor solution.

[0018] In some embodiments, the parameters of the heating treatment are as follows: temperature is 40-80° C., and time is 4-10 h.

[0019] Compared with the prior art, the advantages of the above-mentioned heating treatment process adopted in the present invention are: 40-80°C is a moderate temperature range, which can effectively activate the initiator (such as ammonium persulfate and potassium persulfate), decompose it to produce free radicals, thereby initiating the polymerization reaction of the monomer. This temperature range is neither too high to cause decomposition or excessive cross-linking of the monomer, nor too low to cause the reaction rate to be too slow. At the same time, within this temperature range, heat can be evenly distributed in the entire polymerization precursor solution, ensuring that the polymerization reaction proceeds synchronously at various locations, avoiding local overheating or cold spots, thereby forming a uniform hydrogel network.

[0020] In some embodiments, the post-treatment is to soak or apply the gel with a saline solution, and the post-treatment time is 10-1440 min.

[0021] Compared with the prior art, the present invention adopts the above-mentioned post-treatment process, in which the ions in the salt solution can interact with the functional groups in the hydrogel to form more cross-linking points, thereby increasing the cross-linking density of the hydrogel. This helps to enhance the mechanical strength and toughness of the hydrogel; at the same time, the salt solution can reduce the swelling degree of the hydrogel, making it more stable during the swelling and dehydration process, and avoiding structural damage caused by excessive swelling.

[0022] The third object of the present invention is to provide a high-damping repairable hydrogel for use in the field of high energy dissipation or impact protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a theoretical schematic diagram of the high damping repairable hydrogel of the present invention;

[0024] Figure 2 The stress-strain diagram and Young's modulus diagram of the high damping repairable hydrogel of the present invention;

[0025] Figure 3 is a rheological property diagram of the high damping repairable hydrogel of the present invention;

[0026] Figure 4 This is a graph showing the results of a falling ball impact test on the high-damping repairable hydrogel of the present invention.

[0027] Figure 5 Figure 2. Simulated impact resistance test diagram for the invention of high-damping repairable hydrogel. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0029] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0030] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0031] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0032] Figure 1 It is a theoretical schematic diagram of the high damping repairable hydrogel of the present invention.

[0033] Example 1

[0034] This embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method:

[0035] 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate were dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution. The pH of the hydrogel precursor solution was adjusted to 9. The hydrogel precursor solution was introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and reacted at 60°C for 7 hours to obtain a repairable hydrogel. The repairable hydrogel was then immersed in 1 mol / L sodium sulfate for 24 hours to obtain a high-damping repairable hydrogel PMHB-Na2SO4.

[0036] Example 2

[0037] The present embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate are dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the hydrogel precursor solution is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and the reaction is carried out at 60° C. for 7 hours to obtain a repairable hydrogel, and the repairable hydrogel is then immersed in 1 mol / L potassium sulfate for 24 hours to obtain a high-damping repairable hydrogel PMHB--K2SO4.

[0038] Example 3

[0039] The present embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate are dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the mixture is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and reacted at 60° C. for 7 hours to obtain a repairable hydrogel, and then the repairable hydrogel is immersed in 1 mol / L sodium citrate for 24 hours to obtain a high-damping repairable hydrogel PMHB--Na3Cit.

[0040] Example 4

[0041] The present embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of potassium persulfate are dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the hydrogel precursor solution is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and the reaction is carried out at 60° C. for 7 hours to obtain a repairable hydrogel, and the repairable hydrogel is then immersed in 1 mol / L sodium sulfate for 24 hours to obtain a high-damping repairable hydrogel.

[0042] Example 5

[0043] The present embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate are dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the hydrogel precursor solution is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and the reaction is carried out at 40° C. for 10 hours to obtain a repairable hydrogel, and the repairable hydrogel is then immersed in 1 mol / L sodium sulfate for 24 hours to obtain a high-damping repairable hydrogel.

[0044] Example 6

[0045] The present embodiment provides a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate are dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the hydrogel precursor solution is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and the reaction is carried out at 80° C. for 4 hours to obtain a repairable hydrogel, and the repairable hydrogel is then immersed in 1 mol / L sodium sulfate for 24 hours to obtain a high-damping repairable hydrogel.

[0046] Example 7

[0047] The present embodiment provides a method for repairing a high-damping repairable hydrogel, which is prepared by the following preparation method: 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate are dissolved in 6.18 g of deionized water to prepare a hydrogel precursor solution, the pH of the hydrogel precursor solution is adjusted to 9, the hydrogel precursor solution is introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and the reaction is carried out at 60° C. for 7 hours to obtain a repairable hydrogel, and then the repairable hydrogel is immersed in 1 mol / L sodium sulfate for 24 hours to obtain a high-damping repairable hydrogel PMHB-Na2SO4, the PMHB-Na2SO4 is cut, and a 1 mol / L NaSCN solution is coated on the fracture to obtain PMHB-NaSCN or named PMHB-Na2SO4 (Salt-Welded), and PMHB-NaSCN gel fragments are bonded along the coating to repair the PMHB-Na2SO4. After briefly immersing in 1 mol / L sodium sulfate solution, its damping properties were measured and its impact resistance performance was consistent with that before fracture.

[0048] The present invention performs performance tests on the high damping repairable hydrogels prepared in Examples 1-3, and the test results are shown in Tables 1-4:

[0049] Table 1: Comparison of the damping effects of high-damping repairable hydrogels prepared in Examples 1-3

[0050] Loss factor at room temperature Maximum loss factor Available temperature range (℃) <![CDATA[PMHB-Na2SO4]]> 1.10 1.15 0-70 <![CDATA[PMHB--K2SO4]]> 1.11 1.21 0-70 <![CDATA[PMHB--Na3Cit]]> 0.92 1.45 0-70

[0051] Table 2: Tensile data and Young's modulus of high damping repairable hydrogels prepared in Examples 1-3

[0052] Young's modulus(Mpa) Maximum stretch (%) <![CDATA[PMHB-Na2SO4]]> 95.6±3 172±5 <![CDATA[PMHB--K2SO4]]> 94.2±4 174±6 <![CDATA[PMHB--Na3Cit]]> 252.7±3 57±4

[0053] Table 3: Drop ball impact test results of high damping repairable hydrogels prepared in Examples 1-3

[0054]

[0055] Table 4: Drop ball impact rebound test results of high damping repairable hydrogels prepared in Examples 1-3

[0056]

[0057] It can be seen from the above results that the high-strength and tough hydrogel material provided by the present invention has self-repairing properties and can well avoid the loss of the hydrogel when it is used as an energy dissipation carrier.

[0058] Comparative Example 1

[0059] 3.4 g of methacrylamide, 0.42 g of hydroxyethyl acrylate, 0.072 g of boric acid and 20 mg of ammonium persulfate were dissolved in 6.18 g of deionized water and mixed to prepare a hydrogel precursor solution. The pH of the hydrogel precursor solution was adjusted to 9. The hydrogel precursor solution was introduced into a parallel glass plate mold with a size of 70 mm×700 mm×2 mm, and reacted at 60°C for 7 hours to obtain a repairable hydrogel PMHB.

[0060] Comparative Example 2

[0061] 3.4g methacrylamide, 0.42g hydroxyethyl acrylate, 0.072g boric acid and 20mg ammonium persulfate were dissolved in 6.18g deionized water and mixed to prepare a hydrogel precursor solution. The pH of the hydrogel precursor solution was adjusted to 9, and the hydrogel precursor solution was introduced into a parallel glass plate mold with a size of 70mm×700mm×2mm. The hydrogel was reacted at 60°C for 7 hours to obtain a repairable hydrogel. The repairable hydrogel was then immersed in 1mol / L sodium sulfate for 24 hours to obtain a repairable hydrogel PMHB-NaCl. Its mechanical properties are low, with a Young's modulus of 7.9*10 -5 No damping properties.

[0062] Comparative Example 3

[0063] 3.4g methacrylamide, 0.42g hydroxyethyl acrylate, 0.072g boric acid and 20mg ammonium persulfate were dissolved in 6.18g deionized water and mixed to prepare a hydrogel precursor solution. The pH of the hydrogel precursor solution was adjusted to 9, and the hydrogel precursor solution was introduced into a parallel glass plate mold with a size of 70mm×700mm×2mm. The hydrogel was reacted at 60°C for 7 hours to obtain a repairable hydrogel. The repairable hydrogel was then immersed in 1mol / L sodium sulfate for 24 hours to obtain a repairable hydrogel PMHB-NaBr. Its mechanical properties are low, with a Young's modulus of 4.8*10 -5 No damping properties.

[0064] Furthermore, the inventors tested the tensile strength performance of the samples obtained in Example 1, Example 3, Example 7, and Comparative Examples 1-3. The test results are as follows: Figure 2 As shown, from Figure 2 It can be seen that the hydrogel prepared by the preparation method of the present invention has good tensile properties.

[0065] Furthermore, the inventors tested the rheological properties of the samples obtained in Example 1, Example 3, Example 7 and Comparative Example 1. The test results are as follows: Figure 3 As shown, from Figure 3It can be seen that positioning the PMHB-Na2SO4 hydrogel within the glass transition region provides the greatest damping capacity, with a tan δ peak and a high loss modulus. More importantly, the tan δ of the PMHB-Na2SO4 hydrogel at frequencies above 10 Hz at 30 °C exceeds 1, indicating that most of the impact energy applied to the material can be dissipated within a time scale of less than 0.1 s.

[0066] Furthermore, the inventors conducted a drop ball impact test on the samples prepared in Example 1, Example 3, Example 7 and Comparative Example 1, as well as a blank group, polydimethylsiloxane, D30 and polyurethane foam. The results are as follows: Figure 4 As shown, PMHB-Na2SO4 hydrogel quickly suppressed the shock wave of the ball falling from a height of 70 cm in less than 0.6 s, and its performance was similar to that of the repaired PMHB-Na2SO4 (Salt-Welded), which shows that even if the PMHB-Na2SO4 hydrogel is repaired, its impact performance will not be affected; at the same time, the performance of PMHB-Na2SO4 hydrogel is significantly better than that of the blank sample, as well as PMHB and PMHB-Na3Cit hydrogels.

[0067] Furthermore, the inventors conducted a simulated impact test on the samples prepared in Example 1, and the results are as follows: Figure 5 As shown, from Figure 5 It can be seen that under the protection of PMHB-Na2SO4 hydrogel, the glass plate did not break after being hit by a hammer, indicating that PMHB-Na2SO4 hydrogel has good impact resistance.

[0068] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A high damping repairable hydrogel, characterized in that: The invention comprises the following raw materials: methacrylamide, hydroxyethyl acrylate monomer, boric acid, salt solution and initiator, wherein the mass ratio of the methacrylamide to the hydroxyethyl acrylate monomer is 8:1, the sum of the mass percentages of the methacrylamide and the hydroxyethyl acrylate monomer is taken as the main body, the mass of the initiator is 0.5% of the mass of the main body, the mass of the boric acid is 1.8% of the mass of the main body, and the concentration of the salt solution is 1 mol / L.

2. The high damping repairable hydrogel according to claim 1, characterized in that: The salt solution is selected from at least one of a potassium sulfate solution, a sodium sulfate solution, a sodium citrate solution and a sodium bisulfate solution.

3. The high damping repairable hydrogel according to claim 1, characterized in that: The initiator is ammonium persulfate and / or potassium persulfate.

4. A method for preparing a high damping repairable hydrogel according to any one of claims 1 to 3, characterized in that: The preparation method specifically comprises the following steps: Using water as solvent, methacrylamide, hydroxyethyl acrylate, boric acid and initiator are dissolved in water to prepare a polymerization precursor solution, the polymerization precursor solution is poured into a parallel glass plate mold for heating treatment to obtain a gel, and then the gel is post-treated with a salt solution to obtain a high-damping repairable hydrogel.

5. The method for preparing the high damping repairable hydrogel according to claim 4, characterized in that: The mass of the water is 60%-70% of the mass of the main body.

6. The method for preparing the high damping repairable hydrogel according to claim 4, characterized in that: The pH of the polymerization precursor solution is 9.

7. The method for preparing the high damping repairable hydrogel according to claim 4, characterized in that: The parameters of the heating treatment are as follows: temperature is 40-80°C, and time is 4-10h.

8. The method for preparing the high damping repairable hydrogel according to claim 4, characterized in that: The post-treatment is to soak or apply the gel with a saline solution, and the post-treatment time is 10-1440 minutes.

9. Use of the high-damping repairable hydrogel according to any one of claims 1 to 3 in the field of high energy dissipation or impact protection.